Migration as stressor: loss of status, coping strategies and psychosocial impact - San Juan, César; Vergara, Anabel; Ocáriz, Estefanía (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
In this paper we show the results of a prospective study carried out with immigrant persons in the three main cities of the Basque Country (Spain). It is a diagnosis of their social and professional reality. The needs, future projects, integration difficulties and social impact of immigrant workers is analyzed. We have confirmed that there is a deterioration of their professional status with regard to the one they had in their country of origin. This deterioration, linked to ineffective coping strategies, leads to the appearance of clinical symptoms of anxiety and depression. The mourning for the loss of cultural referents is the most important problem that we have been able to identify. Furthermore, we detect an emotional lack linked to the loss of family ties, customs, climate, etc., and related to the difficulties for making an adequate interpretation of the codes used in the social interactions with the receiving society.